New Development in Catalytic Reforming Process to Produce High Octane Gasoline - Sukkar, Khalid A.; Abd Al-Raheem, Hayam M.; Sabry, Layth S.; Resym, Lattif A. (Journal of Petroleum Research and Studies, 2014)
In this work, improved catalytic reforming reaction was carried out through using reaction promoters Sn, In and Ge. Four types of catalysts were prepared: Pt/HY, Pt-Sn/HY, and Pt-Sn-In/HY, and Pt-Sn-Ge/HY. The weight percentage of metals were 0.5 % for Pt and 0.1% for each of Sn, In and Ge. The performances of catalysts (activity, selectivity and catalyst stability) were studied using Iraqi heavy naphtha of Al-Dura refinery (Baghdad) as feedstock. The catalytic reforming unit consisted of a vertical tubular stainless steel reactor of 20mm internal diameter, 30 mm external diameter and 680 mm height. The operating pressure was atmospheric, and the operating temperatures varied between 425 to 525oC. For all experimental runs: the weight hourly space velocity WHSV =2, the catalyst amount = 50 g, and H2/HC ratio =3. The results showed that the best reforming temperature over all four types of prepared catalysts was 475 oC which gave the highest conversion of heavy naphtha to high octane products (aromatics and branched isomers). It was concluded that the trimetallic catalyst Pt-Sn-In/HY, and Pt-Sn-Ge/HY show high selectivity to desired reforming products with 91.5% and 85% respectively. On the other hand, the Pt-Sn/HY and Pt/HY, catalysts show slectivities of 79% and 74% respectively. The results indicated a clear increase in catalyst stability with high resistance to coke formation for catalysts promoted with In and Ge as a third metal. Also, it was noted that the production of aromatics and isomers are increased for both types of trimetallic catalysts Pt-Sn-In/HY, and Pt-Sn-Ge/HY under the same operating conditions.